Bangladesh import education from New Zealand : opportunities & challenges / Arunima Ghosh Peya, Ershad Ali and Geetha Subramaniam. - Peya, Arunima Ghosh; Ali, Ershad; Subramaniam, Geetha (Universiti Teknologi Mara Selangor, 2016)
Bangladesh is an emerging economy and has been earning about 7% GDP growth during the last two decades. It has 150 universities which can accommodate 3 million students. Every year, about 5 million young students enter university level education. Therefore, about 2 million young people desire to move overseas for higher education. Existing literature focusses on the need for young generation to go overseas for higher education but the challenges as well as opportunities for studying overseas have not been addressed. This study aims to investigate the opportunities and challenges for Bangladeshi students in choosing New Zealand as a study destination.